Covid 19, mortality in the elderly and associated factors - Navarrete-Mejía, Pedro (2022)
Objetive: to determine the variables associated with mortality from COVID 19 in the older adult population. The study: observational study, 521 patients aged 60 years and over with a clinical/laboratory diagnosis of COVID -19; variables included age, sex, priority of care, origin, comorbidities, stay, respiratory and heart rate, SO2, temperature and signs/symptoms. Findings: deaths, higher frequency in July (50.7%), 91.9% priority I/II, age 70.1 ± 7.5 years, male (71.0%), HR 103.7 ± 18.1 beats/min, RF 29.4 ± 6.4 breaths/min (p<0.001), SO2 75.1% ± 14.35 and stay 6.9 days ± 5.7; cough (68.3%), fever (38.0%) and headache (23.3%) most frequent signs/symptoms. Asthma was associated with mortality (p=0.049). Conclusions: The elderly is a priority for public health systems; older, male, with fever, cough and asthma have a poor prognosis against COVID-19.